Nathan W. Daniels diary - Daniels, Nathan W., 1832-1867.; Richmond, Cora L. V. (Cora Linn Victoria), 1840-1923.
Handwritten diary with photographs, illustrations, and newspaper clippings mounted throughout the text in 3 volumes. Includes a typescript of summaries and transcripts of the diaries byC. P. Weaver.
In volume one, Daniels described his Civil War service with an African American regiment, the U.S. Army 2nd Native Guard Infantry Regiment, chiefly while stationed at Ship Island, Miss., and his time in New Orleans, La., during the summer and fall of 1863. In volume two, Daniels discussed military, political, and social affairs in Washington, D.C., during his years in the capital, 1863-1865. Subjects include civil rights, creation of the Freedmen's Bureau (U.S. Bureau of Refugees, Freedmen, and Abandoned Lands) in March 1864, radical Republicans, and the theater.
Volume three was written primarily by Daniels's wife, the Spiritualist medium Cora Hatch (Cora L. V. Richmond). Topics include the Freedmen's Bureau, speaking engagements at African American churches in Washington, D.C., a visit with her family in Cuba, N.Y., and a lecture tour of the Midwest.
Union Army officer and lecturer and advocate for civil rights and the Freedman's Bureau. Married Cora Hatch, Spiritualist medium and lecturer.
Collection material in English.
Keywords: Weaver, C. P., -- 1939-; United States. -- Army. -- Native Guard Infantry Regiment, 2nd (1862-1863); United States. -- Bureau of Refugees, Freedmen, and Abandoned Lands; Republican Party (U.S. : 1854- ); United States -- Politics and government -- 1865-1877.; African American churches -- Washington (D.C.); Civil rights -- United States; Lectures and lecturing -- Middle West; Spiritualism -- United States; Theater -- Washington (D.C.); Cuba (N.Y.) -- History; Louisiana -- History -- Civil War, 1861-1865.; New Orleans (La.) -- History -- Civil War, 1861-1865.; Ship Island (Miss.) -- History; United States -- History -- Civil War, 1861-1865 -- Participation, African American; United States -- Politics and government -- 1861-1865.; United States -- Politics and government -- 1865-1877.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Washington (D.C.) -- Social life and customs; Army officers; Lawyers